Assessing rainwater harvesting potential in a humid and semi-humid region based on a hydrological model - Luo, Kaisheng; Li, Yuanzheng (Journal of hydrology. Regional studies, 2021)
•Climate change and human activities have influenced natural hydrological processes.•Rainwater resources are available fresh water resources.•Drought in arid and semi-arid regions has become widely concerning.•A method of rainwater harvesting potential assessment in humid regions is proposed.•Spatial and temporal distribution of rainfall in humid/semi-humid zones is uneven. The upper regions of the Yangtze River in China. Evaluating the rainwater harvesting potential (RWHP) is essential for alleviating regional drought and water shortage and solving water shortage and water crisis globally. However, previous studies have mainly focused on arid and semi-arid zones, whereas the assessment of RWHP in humid and sub-humid zones during the dry season is lacking. To fill this gap, a soil and water assessment tool based on meteorology, digital elevation model data, soil, land use, and observed streamflow, was constructed for a selected site. Additionally, a method of assessing RWHP in humid and semi-humid zones was proposed. The results indicate that the average annual RWHP throughout the dry season (March-August) in the upper regions of the Yangtze River is 5657.02 × 105 m3, and that for spring and summer are 1766.21 × 105 and 3890.95 × 105 m3, respectively. Regarding the RWHP structure, it was observed that surface runoff (42.59 %) > groundwater recharge (29.53 %) > base-flow (19.43 %) > soil water content (7.16 %) > lateral flow (1.29). The analysis indicated that the spatial distribution of RWHP is consistent with that of drought, and can alleviate agricultural drought. The inter-annual variation of RWHP was relatively stable, exhibiting a weak increasing trend at the seasonal (dry, spring, and summer) and monthly (March–August) scales during 1999–2018. RWHP trends are primarily regulated by rainfall with the trend for a small part of the region being influenced by evapotranspiration. Our study provides a reference for the evaluation of RWHP in dry seasons in humid and semi-humid zones.